2003
DOI: 10.1046/j.1542-474x.2003.08410.x
|View full text |Cite
|
Sign up to set email alerts
|

Variations of Intrathoracic Amount of Blood as a Reason of ECG Voltage Changes

Abstract: Blood redistribution during gravity change leads to changes of QRS voltage, which is more expressed and steady on R in Z lead: an average near 0.2 mV. It is due to the balance between two factors: (a). changes of degree of short circuiting by variations in the amount of blood in thorax (b). changes of distance between heart and electrodes as a result of change in the position, form, and volume of the heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…However, for the Brody effect, an increase in blood volume in the heart should be more than 30%, but such an increase is not observed at short-term hypoxia (Stembridge et al, 2015). The distance from the heart to the recording electrodes on the thorax surface also affects the amplitudes of the cardiopotential (Saltykova et al, 2003). The authors' previous studies showed that in healthy volunteers at acute normobaric hypoxia over 15 minutes there was no significant change in the breath pattern (Zamenina et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…However, for the Brody effect, an increase in blood volume in the heart should be more than 30%, but such an increase is not observed at short-term hypoxia (Stembridge et al, 2015). The distance from the heart to the recording electrodes on the thorax surface also affects the amplitudes of the cardiopotential (Saltykova et al, 2003). The authors' previous studies showed that in healthy volunteers at acute normobaric hypoxia over 15 minutes there was no significant change in the breath pattern (Zamenina et al, 2019).…”
Section: Discussionmentioning
confidence: 98%